Desenvolvimento de sistemas de controle para motores de ímãs permanentes para tração de veículos elétricos - Lazzari, Thiago (2020)
This master thesis presents the development of an experimental setup to drive and control of permanent magnet synchronous motors with external rotor. The main characteristics of these electric motors are related to their high power density and high efficiency. Such characteristics are interesting for applications in the traction system of electric vehicles. There are different configurations of motors in the the electric traction system. A topology that has been calling a lot of attention recently is the in-wheel electric motors of electric vehicles. The use of this configuration presents restrictions on obtaining rotor position information, being necessary the use of Hall effect sensors or sensorless control strategies. Usually, permanent magnet synchronous motors that use the classic control approaches using Hall effect sensors present undesirable torque ripples. Thus, in this master thesis, a strategy will be applied to estimate the speed and position based on the information from Hall effect sensors. These variables are applied in the vector control technique. Sensorless control strategy based on current state observers and back electromotive forces in the stationary reference frame is applied as an alternative control method in case of failure in the position sensors. Finally, simulation and experimental results validate the theoretical analysis developed and demonstrate the performance of the control techniques applied to the permanent magnet synchronous motors.